Association between frailty and C-terminal agrin fragment with 3-month mortality following ST-elevation myocardial infarction - de Souza Ramos, Juan Thomaz Gabriel [UNESP]; Ferrari, Felipe Sanches [UNESP]; Andrade, Morganna Freitas [UNESP]; de Melo, Caroline Souto; Boas, Paulo José Fortes Villas [UNESP]; Costa, Nara Aline; Pereira, Amanda Gomes [UNESP]; Dorna, Mariana Souza [UNESP]; Azevedo, Paula Schmidt [UNESP]; Banerjee, Jay; Phillips, Bethan E.; Atherton, Philip J.; et al. (Elsevier, 2022)
The objective of this study was to evaluate the association between frailty, evaluated by the Clinical Frailty Scale (CFS) and FRAIL scale, and C-terminal agrin fragment (CAF) levels with 3-month mortality following ST-segment elevation myocardial infarction (STEMI). This was a prospective observational study that included patients over the age of 18 years with STEMI admitted to the coronary intensive care unit. Within 48 h of admission, the CFS and FRAIL scale were applied and blood samples collected for serum CAF evaluation. Patients were followed for 3 months after hospital discharge, and mortality was recorded. One hundred and eleven patients were included; mean age was 62.3 ± 12.4 years, 61.3% were male and 11.7% died during the 3 months of follow-up. According to the CFS, 79.3% of the patients were classified as not frail, 12.6% as pre-frail and 8.1% as frail. According to the FRAIL scale, 31.5% of the patients were classified as not frail, 53.2% as pre-frail and 15.3% as frail. In univariate analysis, the CFS but not FRAIL scale was associated with mortality. In multiple logistic regression analysis, pre-frail/frail according to CFS (odds ratio [OR]: 6.118; CI 95%: 1.344–27.848; p = 0.019) and CAF levels (OR: 0.943; CI 95%: 0.896–0.992; p = 0.024) were associated with increased 3-month mortality. In a sub-analysis of 53 patients ≥65 years, CFS and CAF levels were associated with 3-month mortality. In conclusion, CAF levels and frailty determined by the CFS were associated with 3-month mortality after STEMI in the general and older population.
Keywords: Acute myocardial infarction; C-terminal agrin fragment; Clinical frailty scale; FRAIL scale